2019
DOI: 10.1096/fj.201801821r
|View full text |Cite
|
Sign up to set email alerts
|

BMSCs protect against renal ischemia‐reperfusion injury by secreting exosomes loaded with miR‐199a‐5p that target BIP to inhibit endoplasmic reticulum stress at the very early reperfusion stages

Abstract: Bone marrow–derived mesenchymal stem cells (BMSCs) have been recently reported to play a variety of vital roles in organ and tissue damage repair, mainly via potent paracrine activity, including secreting extracellular vesicles, such as exosomes, that serve as mediators facilitating intercellular communication and reprogramming recipient cells by delivering their contents to target cells. However, the underlying mechanisms are diverse and complex, and the influencing characteristics have rarely been studied. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 46 publications
1
55
0
Order By: Relevance
“…A recent study demonstrated, with a myocardial infarction model, that the beneficial effects of MSC transplantation are mediated by exosomes, which shuttled miR-125b-5p by targeting Bnip3 [82]. It has also been found that BMSCs protect against I/R by secreting exosomes loaded with miR-199a-5p by targeting BIP [83]. Another study showed that BMSC-derived exosomes could modulate age-related insulin resistance by the transfer of functional exosomal miR-29b-3p and thereby inhibit the expression of the target gene SIRT1 [84].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated, with a myocardial infarction model, that the beneficial effects of MSC transplantation are mediated by exosomes, which shuttled miR-125b-5p by targeting Bnip3 [82]. It has also been found that BMSCs protect against I/R by secreting exosomes loaded with miR-199a-5p by targeting BIP [83]. Another study showed that BMSC-derived exosomes could modulate age-related insulin resistance by the transfer of functional exosomal miR-29b-3p and thereby inhibit the expression of the target gene SIRT1 [84].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al confirmed that bone marrow MSCs protected against lung IRI by secreting exosomes loaded with miR‐21‐5p . Wang et al manifested that MSCs ameliorated renal IRI in an exosomal miR‐199a‐5p‐dependent manner . Although a growing body of evidence demonstrated the protection of MSCs against hepatic IRI by secreting exosomes, the underlying mechanisms have rarely been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Using the renal I/R model, we discovered that increased ER stress leads to more apoptosis and damage; inhibition of ER stress enhances EV-induced protection against renal I/R injury. A series of studies have shown that the response to increasing unfolded and misfolded proteins causes GRP78 to dissociate from the ER stress sensor, while free GRP78 levels determine the activation of UPR, which may trigger cell death under ER stress [49][50][51][52]. Therefore, the regulation of GRP78 has a close impact on the ER stress process.…”
Section: Discussionmentioning
confidence: 99%